An unexpected SN‘ reaction on cobaltocenium triflates: substitution on one ring and elimination on the other - Grün, Mareile von der; Schaefer, Carsten; Gleiter, Rolf (Organometallics, 2003)
CpCo-capped tetra-n-propylcyclopentadienone complexes were O-alkylated and O-acylated. Reactions of the O-triflated product with organolithium compounds afford a substitution of the Cp ring in 40−80% yield; as products the RCpCo-capped tetra-n-propyl-cyclopentadienone complexes were isolated.